Increased risk of hospitalization and death in Mexican children and adolescents with COVID-19 and comorbidities - Pablo Méndez-Hernández; Diego R. Hernández-Galdamez; Miguel A. González-Block; Daniela K. Romo-Dueñas; Rosa M. Cahuantzi-Tamayo; Omar Texis-Morales; Juan J. Medina-Urzúa; Rosalba Cerón-Meza; Irma A. Hernández-Vicente; Marivel Lumbreras-Guzmán (Permanyer, 2023)
Background: Although COVID-19 (coronavirus disease 2019) in children is usually mild, they need hospitalization and intensive care in exceptional cases. Adverse outcomes have been observed mainly among children with comorbidities, justifying their vaccination. This study aimed to assess the risk of hospitalization and death in Mexican children and adolescents with COVID-19 and comorbidities. Methods: A cross-sectional study was performed on 366,542 confirmed COVID-19 cases under 18 years, reported by the Mexican Ministry of Health up to July 9, 2022. Logistic regression models were performed. Results: The mean age was 10.98 years, 50.6% were male, and 7.3% reported at least one comorbidity. The percentage of hospitalization and death in COVID-19 patients with and without comorbidities was 3.52%, and 0.20%, respectively; children with comorbidities presented a higher percentage of hospitalization (14.0%) and death (1.9%). The probability of hospitalization was 5.6 times greater in pediatric patients with COVID-19 and comorbidities, and the comorbidities that showed the greatest risk were immunosuppression (odds ratio (OR) 22.06), chronic kidney disease (CKD) (11.36), and cardiovascular diseases (5.66). The probability of death in patients with comorbidities was 11.01 times higher than in those without diseases, and the highest risk was observed in those with CKD (OR 12.57), cardiovascular diseases (6.87), and diabetes (5.83). Conclusions: Pediatric patients with comorbidities presented a higher risk of severe COVID-19. It is suggested that vaccination should be promoted with greater emphasis on pediatric patients with comorbidities.